La tradición oral de Pasco-Perú: una experiencia de investigación cualitativa - Salazar Espinoza, David Elí (2021)
The article has the purpose of showing qualitative research advances on the oral tradition of Pasco that we have been doing at UNDAC-Pasco. We review theoretical currents on oral tradition in the contemporary academic world, we give an account of the preliminary work that has been done in Pasco, we show some results, those that affect the social imagination and how these texts circulate in the current community. Methodologically, we resort to hermeneutics to analyze and interpret texts from a literary perspective, ethnography to collect the source of the informants, we systematize the information and explain a text. The intention is to publish it.